Bone mineral density of the mandible as predictor of osteoporosis among Malays - Kamaruddin, Noorshaida (2021)
Relationship between craniofacial bone strength and other skeletal bone associated with osteoporosis were studied by measuring bone mineral density (BMD). The aim of this study is to compare and correlate the bone density of the mandible and other skeletal bone using Dual Energy X-ray Absorptiometry (DXA) and Cone Beam Computed Tomography (CBCT). The sensitivity of TLD 100H exposed to DXA also tested. For comparison of BMD value, the head phantom was scanned with different data acquisition protocol and patient positioning for mandibular DXA examination. For correlation of mandible with other skeletal bone, patient who had underwent CBCT examination underwent DXA examination of mandible, spine and hip. Linear measurement was then being made on the CBCT images of patients. The result from the measurement of CBCT image along with the result from DXA examination was taken for statistical analysis. The data was analysed using T-test, Pearson’s correlation, Spearman’s correlation, Kruskal Wallis and Mann Whitney. The result shows that there is no significant difference in BMD value using different data acquisition protocol and there was significant difference in BMD value using different positioning when scanning using DXA scanner. The study also found that there was no significant correlation between BMD of the mandible and other skeletal sites from DXA and significant difference was found between density of the mandible from CBCT and DXA. A strong negative correlation exists between computed tomography mandibular index inferior (CTI I) and computed tomography mandibular index superior (CTI S) with bone status (spine). As for TLD, sensitivity of TLD-100H compared TLD-100 was about 23 times higher when exposed to general radiography x-ray and 1.26 times when exposed to DXA energy. In conclusion, the evaluation of mandibular density to predict osteoporosis is possible using CTI I and CTI S indices.